2016
DOI: 10.1055/s-0036-1586734
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Evoked Potential Mismatch Negativity in Normal-Hearing Adults

Abstract: Introduction  Mismatch Negativity (MMN) corresponds to a response of the central auditory nervous system. Objective  The objective of this study is to analyze MMN latencies and amplitudes in normal-hearing adults and compare the results between ears, gender and hand dominance. Methods  This is a cross-sectional study. Forty subjects participated, 20 women and 20 men, aged 18 to 29 years and having normal auditory thresholds. A frequency of 1000Hz (standard stimuli) and 2000Hz (deviant stimuli) was used to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 32 publications
2
14
1
9
Order By: Relevance
“…However, it contradicts other findings, 4 which found lower latencies and higher amplitudes in women for stimuli that differed in frequency, although they did not perform gender analysis. And yet another study, 27 which also showed a difference between genders regarding latency, being higher for men.For amplitude, no significant difference was found, as occurred in the current study.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, it contradicts other findings, 4 which found lower latencies and higher amplitudes in women for stimuli that differed in frequency, although they did not perform gender analysis. And yet another study, 27 which also showed a difference between genders regarding latency, being higher for men.For amplitude, no significant difference was found, as occurred in the current study.…”
Section: Discussionmentioning
confidence: 90%
“…However, other authors showed an even larger average amplitude. 27 When evaluating illiterate individuals, and after 1 year of study, Schaadt et al observed an increase in the amplitude with verbal stimulation after literacy. 32 However, the results were lower than those found in the present study, probably because the current sample had at least 8 years of schooling, which may have contributed to the amplitude being greater than that presented in the aforementioned study.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 These potentials are most commonly used to evaluate auditory abilities objectively. [3][4][5] The long latency auditory evoked potential (LLAEP) record shows a sequence of negative (N) and positive (P) peaks, among which are the potential P1-N1-P2-N2-P300 and mismatch negativity (MMN). The P1-N1-P2 complex represent the corti-cal potentials and provide information on the arrival on the auditory stimuli to the cortex.…”
Section: Introductionmentioning
confidence: 99%
“…This potential has as main generator the auditory cortex and receives contributions from the frontal cortex, thalamus and hippocampus (8) . It is a cerebral automatic response, promoted by any discriminable change in some repetitive aspect of auditory stimulation (6,9,10,11) , indicating a mismatch between the new sensory input, in relation to a stored standard stimulus In the short-term auditory sensorial memory (1,6,12) . MMN is obtained by subtracting the response evoked by the rare stimulus in relation to the standard stimulus presented (4,9,10) , and the result appears as a wave with negativity (6,9) .…”
Section: Introductionmentioning
confidence: 99%
“…MMN is a procedure that has a good correlation with the results found in subjective evaluations that, similarly, analyzed the ability of auditory discrimination (6,13) . Its main advantage, compared to other exams, is that the wave appears independently of the attention of the individual to the presented sound stimuli (1,4,6,7,10,14) , that is, it can be registered without the influence of the attention of the subject and without requiring tasks, making it particularly suitable for clinical studies in evaluating the child population (4,11) . Studies have shown that MMN can be a very useful evaluative means for recognizing changes in language (4,9) in children due to the possibility of assessing auditory processing deficit at an early age (9,13,15) Capable of analyzing neurophysiological plasticity (13) .…”
Section: Introductionmentioning
confidence: 99%